2003
DOI: 10.1016/s0012-821x(02)01155-x
|View full text |Cite
|
Sign up to set email alerts
|

Modern spectral climate patterns in rhythmically deposited argillites of the Gowganda Formation (Early Proterozoic), southern Ontario, Canada

Abstract: Rhythmically deposited argillites of the Gowganda Formation (ca. 2.0^2.5 Ga) probably formed in a glacial setting. Drop stones and layered sedimentary couplets in the rock presumably indicate formation in a lacustrine environment with repeating freeze^thaw cycles. It is plausible that temporal variations in the thickness of sedimentary layers are related to interannual climatic variability, e.g. average seasonal temperature could have influenced melting and the amount of sediment source material carried to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…A -The "varves" in the Gowganda Formation are commonly subdivided into many thin, repetitive "couplets" of very thin light layers with large grain size and thick dark layers with small grain size, displaying no evidence of periodic yearly variation; B -Close-up photograph showing laminae with two light grains marked; C -Near close-up photograph showing a light lamina with large grains and dark laminae above and below (Site 1, at Cobalt). Compare with illustrations inJackson (1965),Hughes et al (2003),Melezhik et al (2013),Williams et al (2016) and especially to turbidite rhythmites described byEyles & Januszczak (2007, fig. 13).…”
mentioning
confidence: 51%
“…A -The "varves" in the Gowganda Formation are commonly subdivided into many thin, repetitive "couplets" of very thin light layers with large grain size and thick dark layers with small grain size, displaying no evidence of periodic yearly variation; B -Close-up photograph showing laminae with two light grains marked; C -Near close-up photograph showing a light lamina with large grains and dark laminae above and below (Site 1, at Cobalt). Compare with illustrations inJackson (1965),Hughes et al (2003),Melezhik et al (2013),Williams et al (2016) and especially to turbidite rhythmites described byEyles & Januszczak (2007, fig. 13).…”
mentioning
confidence: 51%
“…No convincing evidence for solar cycles older than 1500 myr has been reported before. Both Hughes et al 13 and Dmitriev et al 59 reported potential records of solar cycles based on the same part of argillite strata in mid-Paleoproterozoic Gowganda Formation. However, neither studies have considered red noise when analysing climatic time series, nor did they provide any depositional rate constraints to support their varve interpretation of the couplets.…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that some of the Earth's climatic cycles are coupled to the solar cycles 6 . Such cyclic climatic variations are revealed in sedimentary archives of Cenozoic 7 , Mesozoic 8 , Paleozoic 9 , Neoproterozoic 10 , and Mesoproterozoic 11 , but no convincing evidence from older sediment records 12,13 . When did the Sun's magnetic field exhibit stabilized cycles?…”
mentioning
confidence: 99%
“…It has been suggested by a number of workers (Jackson, 1965;Lindsey, 1969;Young, 2001;Hughes et al, 2003) that there are varved deposits in some northern outcrops of the Gowganda Formation. If this interpretation is correct, it suggests that seasonal differences were sufficiently strong to produce alternating freezing and thawing in pro-glacial lakes, the warm seasons permitting deposition of coarser material including ice-rafted cobbles and boulders.…”
Section: Seasonality and Glaciations At Low Palaeolatitudes?mentioning
confidence: 99%